Sejarah Tokoh-Tokoh Psikologi Pendidikan yang Membentuk Pendidikan Modern - Weni Massang (Journal of Applied Psychology and Health Studies, 2025)
This study discusses seven educational psychology figures who made fundamental contributions to the understanding of the learning process and human cognitive development. These figures include Jean Piaget with his theory of cognitive development, Lev Vygotsky with his sociocultural theory, B.F. Skinner with behaviorism and programmed learning, Jerome Bruner with his theory of discovery learning, John Dewey with the concept of learning by doing, Howard Gardner with his theory of multiple intelligences, and David Ausubel with his theory of meaningful learning. Each of these theories offers a unique perspective on how humans learn and develop, which has shaped the foundation of modern educational practices. These theories complement one another and provide a comprehensive framework for understanding the learning process from various viewpoints: cognitive, social, behavioral, and constructivist.